Saved by the matchmaker - Hedlund, Jody (Hedlund, Jody. Shanahan match, 2024)
"Enya Shanahan's ill-fated marriage has left her with an annulment and a child on the way. Her father's solution is for her to marry again, and the local matchmaker knows just the man: Captain Sullivan O'Brien. Enya's heart is closed off to love in this marriage of convenience, but a greater purpose draws them together"--